International Façades - CROFT - Marcel Bilow (A+BE: Architecture and the Built Environment)
Looking at Central European building projects illustrates an awareness of sustainability and the need to save energy. This trend is based on the finiteness of natural resources, and is thus wise to follow. Developments in this region including passive house technologies, and energy plus solutions that create more energy than they use have become realisable. But it is not increasing technological knowledge alone that supported these developments; the Central European climate makes it possible to invent technological solutions that allow for maximum comfort while maintaining low energy consumption.